PENGARUH AKUNTABILITAS DAN TRANSPARANSI TERHADAP KINERJA PENGELOLAAN ANGGARAN BADAN PERENCANAAN PEMBANGUNAN PENELITIAN DAN PENGEMBANGAN PROVINSI SUMATERA UTARA DENGAN EFEKTIVITAS SISTEM INFORMASI PEMERINTAH DAERAH SEBAGAI VARIABEL MODERASI - Hanifah, Luthfiah; Januri, Januri; Hanum, Zulia (UNIVERSITAS DHARMAWANGSA, 2025)
This study aims to analyze the influence of accountability and transparency on budget management performance at the Regional Development Planning, Research, and Development Agency of North Sumatra Province. In particular, the research examines how the effectiveness of the Regional Government Information System functions as a moderating variable that can strengthen the relationship between the independent variables and the dependent variable. To achieve this objective, the study adopts a quantitative associative research design, which is appropriate for identifying causal relationships between variables. The analysis is conducted using moderation regression techniques, allowing the researcher to test both the direct effects of accountability and transparency on budget management performance, as well as the interaction effects when moderated by Regional Government Information System. This methodological approach provides a comprehensive understanding of whether and how digital governance systems enhance the impact of accountability and transparency on improving budgetary outcomes within the public sector. The research findings indicate that accountability has a positive and significant effect on budget management performance. The results of the study show that accountability has a significant and positive effect on budget management performance, which means that an increase in accountability will significantly improve performance. Transparency is also proven to have a significant and positive effect on budget management performance, indicating that the higher the level of transparency, the better the budget management performance. In addition, the moderation test results show that SiPD strengthens the influence of both accountability and transparency on budget management performance.